2013
DOI: 10.1016/j.cell.2013.10.042
|View full text |Cite|
|
Sign up to set email alerts
|

Δ9-THC-Caused Synaptic and Memory Impairments Are Mediated through COX-2 Signaling

Abstract: SUMMARY Marijuana has been used for thousands of years as a treatment for medical conditions. However, untoward side effects limit its medical value. Here we show that synaptic and cognitive impairments following repeated exposure to Δ9-tetrahydrocannabinol (Δ9-THC) are associated with the induction of cyclooxygenase-2 (COX-2), an inducible enzyme that converts arachidonic acid to prostanoids, in the brain. COX-2 induction by Δ9-THC is mediated via CB1 receptor-coupled G-protein βγ subunits. Pharmacological or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
149
3
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(158 citation statements)
references
References 69 publications
3
149
3
3
Order By: Relevance
“…19,25 Briefly, after decapitation, brains were rapidly removed and placed in cold oxygenated (95% O 2 , 5% CO 2 ) artificial cerebrospinal fluid (ACSF) containing (mM) 125.0 NaCl, 2.5 KCl, 1.0 MgCl 2 , 25.0 NaHCO 3 , 1.25 NaH 2 PO 4 , 2.0 CaCl 2 , 25.0 glucose, 3 pyruvic acid and 1 ascorbic acid. Slices were cut at a thickness of 350 to 400 μm and transferred to a holding chamber in an incubator containing ACSF at 36°C for 0.5 to 1 hour, and maintained in an incubator containing oxygenated ACSF at room temperature (~22 to 24°C) for 41.5 hours before recordings.…”
Section: Hippocampal Slice Preparationmentioning
confidence: 99%
See 3 more Smart Citations
“…19,25 Briefly, after decapitation, brains were rapidly removed and placed in cold oxygenated (95% O 2 , 5% CO 2 ) artificial cerebrospinal fluid (ACSF) containing (mM) 125.0 NaCl, 2.5 KCl, 1.0 MgCl 2 , 25.0 NaHCO 3 , 1.25 NaH 2 PO 4 , 2.0 CaCl 2 , 25.0 glucose, 3 pyruvic acid and 1 ascorbic acid. Slices were cut at a thickness of 350 to 400 μm and transferred to a holding chamber in an incubator containing ACSF at 36°C for 0.5 to 1 hour, and maintained in an incubator containing oxygenated ACSF at room temperature (~22 to 24°C) for 41.5 hours before recordings.…”
Section: Hippocampal Slice Preparationmentioning
confidence: 99%
“…Long-term potentiation (LTP) at CA3-CA1 synapses was induced by high-frequency stimulation, as described previously. 19,25 The input-output function was tested before recording LTP, and the baseline stimulation strength was set to provide field excitatory postsynaptic potential with an amplitude of~30% from the subthreshold maximum derived from the input-output function.…”
Section: Electrophysiological Recordingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Beneficial effects in preclinical studies involved CB 1 R and/or CB 2 R, the selective activation of which was found to be effective in improving cognitive impairment, preserving neuronal cells, and preventing Aβ-induced microglial activation and the generation of proinflammatory mediators, as well as removing pathological deposits in different in vivo and in vitro models of AD [86][87][88][89][90]. In addition, beneficial effects of cannabinoids in AD may also be, at least partially, related to the activation of PPAR nuclear receptors for which certain cannabinoids may serve as ligands [88,91], whereas, in the case of some particular cannabinoids (e.g., antioxidant phytocannabinoids), they may exert some more specific effects in relation with AD pathogenesis, for example: 1) by preventing Aβ aggregation, thereby hindering plaque formation and reducing the density of neuritic plaques due to inhibition of acetylcholinesterase activity or increased expression of neprilysin, an enzyme in the Aβ degradation cascade [86,[91][92][93][94]; and 2) by inhibiting Aβ-induced tau protein hyperphosphorylation by glycogen synthase kinase-3β [82][83][84]. Some recent studies have also highlighted the interest of targeting endocannabinoid inactivation in AD, through strategies of genetic inactivation [e.g., mice deficient in monoacylglycerol lipase (MAGL) or fatty acid amide hydrolase (FAAH)] or by inhibiting these enzymes (e.g., JZL184, URB597, respectively) [95][96][97][98].…”
Section: Cannabinoids and Brain Damage In The Immature Brain: Neonatamentioning
confidence: 99%